A Survey of Customer Loyalty in U.P Organized Retail Stores - Singh, Shilpi; Kumar, J (International Journal of Psychosocial Rehabilitation, 2020)
This paper provides a broad overview of the structure and direction of the factors that keeps customer loyal in the state of Uttar Pradesh in retail stores. The paper addresses research gaps that exist within the literature of the expectations and consumption of a quality product in the organized retail sectors. On the basis of this gap analysis, current research problem got identified. The major three constructs of the study were retail service quality, and customer loyalty. From this research problem, few research questions were derived, followed by study objective setting. Based on past literature support, one conceptual model were developed and presented in this paper. Besides, formulated hypotheses, relevance of the study, study design & methods, scope, etc were discussed in this paper. According to the survey, consumer loyalty is most strongly influenced by the quality of the product and its value. According to industry perception, the majority of consumers want personalization, yet our analysis shows that there is a discrepancy between rhetoric and reality.